Epidemiological studies of canine ehrlichiosis and babesiosis in Andhra Pradesh - Mounika, Bana; Y Chaitanya; K Sudhakar Goud; L Jeyabal (Indian Journal of Veterinary Medicine, 2024)
The present study was aimed to report the prevalence of canine ehrlichiosis and babesiosis in dogs. Overall prevalence of canine ehrlichiosis and babesiosis was 28.23 per cent (35/124) based on polymerase chain reaction (PCR). Among 35 dogs, 20 (57.14%) were affected with canine ehrlichiosis, 11 (31.43%) with canine babesiosis and 4 (11.43%) with concurrent ehrlichiosis and babesiosis. Canine ehrlichiosis (45%) and babesiosis (63.64%) was found to be higher in dogs below 2 years of age. Breed wise prevalence of canine ehrlichiosis and canine babesiosis was highest in Labrador retriever. The occurrence was higher in males (68.57%) compared to females (31.43%) in canine ehrlichiosis and babesiosis.